4.5SI and 4.5SH RNAs: Expression in various rodent organs and abundance and distribution in the cell - Tatosyan, K. A.; Koval, A. P.; Gogolevskaya, I. K.; Kramerov, D. A. (Molecular biology (New York), 2017)
Studying the structure, functions, and cell physiology of small RNAs remains important. The 4.5SI and 4.5SH small RNAs, which were among the first to be discovered and sequenced, share several features, i.e., they are both approximately 100 nt in size, are synthesized by RNA polymerase III, and are found only in rodents of several related families. Genes coding for these RNAs are evolutionarily related to short interspersed elements (SINEs). However, the two RNAs differ in nucleotide sequence, half-life in the cell, and the organization of their genes in the genome. Although the 4.5SI and 4.5SH RNAs have been identified more than three decades ago, several aspects of their metabolism in the cell are still poorly understood. The 4.5SI and 4.5SH RNA levels were measured in various organs of three rodent species (mouse, rat, and hamster). Both of the RNAs were found to occur at high levels, which were much the same in different organs in the case of the 4.5SI RNA and varied among organs in the case of the 4.5SH RNA. Both 4.5SI and 4.5SH RNAs demonstrated a predominantly nuclear localization with a detectable presence in the cytoplasm. The copy number per cell for the RNAs was estimated at 0.4‒2.4 × 10 6 . A quantitative study for the 4.5SI and 4.5SH RNAs was performed for the first time and resolved a number of contradictions in data from other studies.